Digital-Based Guidance for Reciting and Memorizing the Qur'an for Children in Curug Village, Kandanghaur District, Indramayu Regency - Hafaf Fadilah (Konsultan Jurnal Ilmiah Indonesia, 2025)
In the development of the modern world, young children prefer to hold gadgets rather than drawing books and colored pencils. Learning the Koran at an early age is an obligation that must be carried out and developed by every Muslim individual. This is the basic argument for establishing reading skills as the first and main priority in Islamic education. It is common knowledge that interest in learning, especially learning to read the Koran, among some school-age children in Indonesia is decreasing. Especially school-aged children aged 7-12 years who still enjoy playing, trying new things and attracting the attention of other people. Children who go to formal school do not necessarily know how to read the Koran and there are still many who are illiterate in the Koran. However, they are still easily influenced by their friends' social environment. The influence of the lack of Al-Qur'an learning still occurs in Curug Village. So one form of student contribution in growing the quality of society is by participating in the Wiralodra University KKN program.